2003
DOI: 10.1161/01.res.0000103863.40055.e8
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Imaging of Myocardial Viability

Abstract: Abstract-Complete knowledge of myocardial structure, metabolism, and function is crucial to understanding the response of the heart to injury such as ischemia. Increasingly, this type of knowledge is required at multiple levels, from that of the isolated myocyte to the functioning organism, to provide basic scientists and clinical investigators a common framework for translation of findings and information feedback. This article focuses on the utilization of imaging methods to assess myocardial viability in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(13 citation statements)
references
References 143 publications
(140 reference statements)
1
12
0
Order By: Relevance
“…However, since the results were from post-myocardial infarction patients, it remains unclear whether the findings can be extended to all patients with a CTO lesion. Delayed hyperenhancement in a chronic collagenous myocardial scar results from an accumulation of contrast media in the interstitial space between collagen fibers, resulting in an increased volume of contrast distribution in the scar tissue compared with that of tightly packed myocytes[26]. The present study showed that the location of the early perfusion defect region identified by MSCT was corresponded to the nuclide filling defect on stressed 201 TI-SPECT perfusion imaging.…”
Section: Discussionsupporting
confidence: 51%
“…However, since the results were from post-myocardial infarction patients, it remains unclear whether the findings can be extended to all patients with a CTO lesion. Delayed hyperenhancement in a chronic collagenous myocardial scar results from an accumulation of contrast media in the interstitial space between collagen fibers, resulting in an increased volume of contrast distribution in the scar tissue compared with that of tightly packed myocytes[26]. The present study showed that the location of the early perfusion defect region identified by MSCT was corresponded to the nuclide filling defect on stressed 201 TI-SPECT perfusion imaging.…”
Section: Discussionsupporting
confidence: 51%
“…Emerging experimental and clinical investigations hold promise for the detection of myocardial fibrosis derived from noninvasive myocardial viability assessment by using contrast-enhanced magnetic resonance (MR) imaging techniques (1214). Late gadolinium (Gd) enhancement MR protocols use a T 1 -weighted inversion recovery–prepared fast gradient echo with imaging performed 10 to 20 min after the intravenous administration of an extracellular Gd-based contrast agent (13).…”
mentioning
confidence: 99%
“…On first-pass images, normal myocardium with normal perfusion would be enhanced by the contrast agent, whereas infarcted regions would appear hypoenhanced due to reduced or absent perfusion. However, the hypoenhanced region would gradually become hyperenhanced as a consequence of increased retention of contrast agent, which is thought to be caused by increased extracellular matrix within collagenous scar, and delayed washout due to reduced capillary density [56]. This method is well-validated clinically for predicting the distribution of infarcted myocardium [57] and for excluding irreversible damage where no delayed enhancement is observed [58, 59].…”
Section: Techniques For Assessing Cardiac Physiologymentioning
confidence: 99%